Connecting Energetic Nitropyrazole and Nitrobenzene Moieties with C−C Bonds using Suzuki Cross‐Coupling Reaction: A Novel Route to Thermally Stable Energetic Materials. Issue 11 (25th October 2022) - Pandey, Krishna; Bhatia, Prachi; Dolui, Pritam; Ghule, Vikas D.; Kumar, Dheeraj
Abstract: This work describes a new route to thermally stable energetic materials by connecting different types of energetic moieties (nitropyrazole and polynitrobenzene) with C−C bonds, where the first step involves a Suzuki cross‐coupling reaction between 4‐bromo‐3, 5‐dinitro‐1H‐pyrazole and 4‐chlorophenylboronic acid. Further nitration, amination, oxidation, and salt formation reactions on the resulting C−C coupled framework resulted in various thermally stable energetic materials. All the compounds were fully characterized using IR, NMR [ 1 H, 13 C{ 1 H}], differential scanning calorimetry (DSC), elemental analysis, and HRMS studies. Compounds 7 and 9 were further characterized by 15 N NMR, and compounds 3 and 6 were characterized by single‐crystal X‐ray diffraction studies. Theoretical heats of formation and energetic performance for all the energetic compounds were calculated using Gaussian 09 and EXPLO5 v6.06 programs, respectively. This research introduces a novel method for synthesizing C−C coupled energetic materials that are not accessible by any other routes. Abstract : This work demonstrates the synthesis and characterization of heat‐resistant explosives using Suzuki Cross‐Coupling reactions.